RASIO KEKAKUAN LENTUR (FLEXURAL STIFFNESS RATIO) ELEMEN BETON AKIBAT GEMPA BERDASARKAN ANALISIS DINAMIK STRUKTUR SINGLE DEGREE OF FREEDOM (SDOF) - Widodo Pawirodikromo; Anggit Mas Arifudin; Dewi Ayu Harjani (TEKNISIA, 2021)
Modeling the effective stiffness of reinforced concrete elements for structural analysis is an important problem and needs to be solved. The effective stiffness is then expressed in terms of the average flexural stiffness ratio Ck. whose value has been determined by Codes. Previous studies have shown that the stiffness ratio is assumed/stated to be strength-dependent. Based on this statement, research on the flexural stiffness ratio Ck of reinforced concrete elements through dynamic analysis of the SDOF structure was carried out. The SDOF structural model used has a vibration period T = 0.48 sec. The dynamic load used is 50 earthquake records consisting of 3-groups of frequency content (low, moderate, high). The dynamic analysis that was carried out has accommodated the inelastic responses whose behavior follows Modified Takeda hysteretic loops. The study results showed that the maximum response of the structure generally occurred in the strong middle part of the earthquake recording or the period of the effective duration of D595. The main finding in this study is that the strength dependent of flexural stiffness is proven. The relationship between the average flexural stiffness ratio Ck and peak ground acceleration of PGA can be mathematically expressed in the equation Ck = -0.981.PGA + 0.822. The relationship is negative, meaning that the higher the PGA value, the smaller the Ck value with a correlation coefficient of R = 0.635 (moderate correlation). The Ck value negatively correlates with the drift ratio and damage index, DI.